Saving Trends and Behaviour in OECD Countries - Dean, Andrew (OECD Publishing, 1989)
National saving ratios are generally lower now than in the 1960s or 1970s. This paper first reviews developments in national and international saving and investment trends in OECD countries since the 1960s. It then examines sectoral saving trends and considers the links between them. There are seen to be important offsets between government and private sector saving and, within the latter, between the business sector and households, so that national and private saving rates tend to be more stable than their component parts. The paper looks in particular at the reasons lying behind the volatile behaviour of household saving in certain countries in recent years ...
Keywords: Economics